Gluten-free laminated baked products: effect of ingredients and emulsifiers on technological quality - de la Horra, Ana Elizabeth (2018)
The aim of this work was to assess the effect of ingredients and emulsifiers on the physical and textural attributes of gluten-free laminated dough pieces and products. Gluten-free flours (soy, rice and cassava), different water levels (76, 68 and 60%), fat samples and emulsifiers (sodium stearoyl lactylate - SSL and diacetyl tartaric acid ester of mono and diglycerides - DATEM) were used to elaborate dough pieces and baked products. Laminated dough samples based on rice/cassava/soy (35:45:20), 60% of water and shortening, presented a high resistance to deformation and showed an inner sheeted structure after baking. The incorporation of the higher doses of SSL and DATEM leads to products of greater specific volume and a tortuous inner conformation due to their layered conformation. This work provides new perspectives into the study of additives with specific action over the components of gluten-free flours and starches, to develop laminated optimum quality products.